Thermophysical properties of carabeef - Flores, Floirendo P. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
We measured the thermophysical properties of both fresh and dried carabeef conditioned to approximately 70%, 60%, 50%, 40% and 30% moisture content (MC), wet basis, by intermittent drying at 70°C, atmospheric pressure. Carabeef was found to contain 78.25% water, 1.17% fat, 1.09% ash and 19.54% protein. Apparent densities by water displacement ranged from 1025.74-1111.46 kg m -3 and followed a third-order polynomial. True densities were higher and behaved linearly with MC. Porosity development was investigated and modeled with a third-order polynomial. Specific heat was determined by the method of mixtures. Underpredicted values were within 1.61-3.02 kJ/kg-°C and were linear with MC. We devised a portable heated probe to measure thermal conductivity (TC) by the line heat source method for both parallel and perpendicular muscle fibers. TC values ranged from 0.27-0.38 W/m-°C and were not significantly affected by fiber orientation. Results correlated with MC via a third-order polynomial. Thermal diffusivity (TD) was computed using experimental values of apparent density, specific heat and TC from the heated probe method, perpendicular geometry. An average value of 1.19 × 10 -6 m2s-1 was calculated.